Total potentiation level: a new metric for quantifying post-activation potentiation dynamics using tensiomyography and statistical parametric mapping - Đorđević, Srđan; Mastnak, Elijan; Žumer, Jan; Krašna, Simon; Ćirić, Maja; Dopsaj, Milivoj (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionPost-activation potentiation (PAP), a transient increase in muscle twitch force after conditioning stimuli, may influence performance. Traditional discrete metrics often fail to resolve PAP’s time-dependent contractility changes. We introduce Total Potentiation Level (TPL)—the integrated area of significant potentiation over time derived from statistical parametric mapping (SPM) of tensiomyography (TMG) data in the rectus femoris—to quantify PAP holistically. We hypothesized that this romisingSPM-based TPL approach would more sensitively capture PAP’s temporal dynamics than traditional discrete measures.MethodsFifty-eight physically active adults (36M/22F; 28.4 ± 11.0 years; normalized knee torque 1.395 ± 0.158Nm/kg) performed four sets of eight incline squats (ISQ) with individualized loads (10RM-based) and 150-s inter-set rest. TMG assessed rectus femoris twitch responses pre/post-ISQ. SPM analyzed potentiation profiles, with TPL derived from supra-threshold SPM t-continuum. TPL’s sensitivity to PAP dynamics was compared to traditional discrete metrics.ResultsSPM analysis indicated that potentiation was maximized following the second ISQ set (TPL = 636.5; p < 0.0001), then plateaued with a slight decline by the fourth set. Statistically significant temporal changes in PAP were observed between 11.3 m and 62.6 m, a detail not discernible through conventional discrete measures. This suggests that TPL may offer enhanced sensitivity in identifying peak potentiation and early fatigue onset.DiscussionThe findings suggest that TMG combined with SPM provides an approach for PAP quantification, with TPL potentially offering a comprehensive view of potentiation dynamics. TPL captures nuanced, continuous temporal changes not readily apparent in traditional discrete analyses and may inform more precise conditioning strategies. Further research is warranted to confirm these preliminary observations and explore broader applications.ConclusionWe developed TPL by combining tensiomyography TMG and statistical parametric mapping SPM. TPL uses SPM’s dynamic time-amplitude analysis to detect subtle, transient PAP shifts, enabling precise neuromuscular adaptation quantification. Its applications may span training, rehabilitation, and aging-related interventions by potentially optimizing conditioning parameters to enhance muscle contractility with minimal fatigue. TPL could also help identify optimal individualized loads to maximize contractile performance, with potential benefits for athletic and therapeutic outcomes and load management. Further studies are needed to validate TPL across various exercise modalities and populations, thereby increasing its applicability to tailored applications.